Gain spectra of lasers based on transitional dimension active region. (December 2020) - Kornyshov, G O; Gordeev, N Yu; Payusov, A S; Serin, A A; Shernyakov, Yu M; Mintairov, S A; Kalyuzhnyy, N A; Maximov, M V; Zhukov, A E
Abstract: We present an experimental study of the optical gain of edge-emitting lasers based on a new type of quantum-sized InGaAs active medium grown on GaAs substrates, which we refer to as quantum-well-dots (QWDs). It is shown that the single layer QWD active region provide at least 33 cm −1 optical gain at 1030 nm comparable to the values typical for InGaAs quantum wells (QWs), and the width of the gain spectra characteristic for InAs quantum dots (QDs). Thus, QWD active region combines the advantages of both QW and QD heterostructures and has a great potential for improving characteristics of various semiconductor devices.